PERKEMBANGAN AKHIR MASA ANAK-ANAK - Tasya Amanda Putri; Vera Novrianti, Rahma Dini, Linda Yarni (CV. ADIBA AISHA AMIRA, 2024)
Childhood does not just end like that, but begins with a very difficult period, which generally appears around the age of three. It is said that this is a difficult or difficult time, because for parents who do not know their child's development, this is indeed the right thing. -really makes things difficult, because their nature is completely different from the others. Children, who always obey and obey their parents every day, have now completely turned into argumentative, resistant, disobedient, dirty, stubborn, (queen queens, in Javanese) and trotz (in German). The aims of this research are: 1) To find out how language development (speech ability) occurs in late childhood. 2) To find out how emotional development occurs in late childhood. 3) To find out how social development occurs in late childhood.This research uses qualitative methods and a case study approach. The main techniques for collecting data are observation and in-depth interviews. The research results obtained show that with the broadening of children's social horizons, children find that speaking is an important means of gaining a place in the group. This creates a strong urge to speak better.